2021
DOI: 10.3390/plants10030520
|View full text |Cite
|
Sign up to set email alerts
|

Short Rotation Intensive Culture of Willow, Spent Mushroom Substrate and Ramial Chipped Wood for Bioremediation of a Contaminated Site Used for Land Farming Activities of a Former Petrochemical Plant

Abstract: The aim of this study was to investigate the bioremediation impacts of willows grown in short rotation intensive culture (SRIC) and supplemented or not with spent mushroom substrate (SMS) and ramial chipped wood (RCW). Results did not show that SMS significantly improved either biomass production or phytoremediation efficiency. After the three growing seasons, RCW-amended S. miyabeana accumulated significantly more Zn in the shoots, and greater increases of some PAHs were found in the soil of RCW-amended plots… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 108 publications
1
14
0
1
Order By: Relevance
“…In past phytoremediation field experiments, our study group has observed stable, but also increased soil pollutant concentrations under a specific willow plantation (Salix miyabeana 'SX61' and 'SX64'), even after almost a decade of cultivation [6,17], contrary to initial hypotheses and objectives. The main findings concerning the establishment (first year) of this plantation can be found in Guidi et al [6].…”
Section: Introductionmentioning
confidence: 66%
See 4 more Smart Citations
“…In past phytoremediation field experiments, our study group has observed stable, but also increased soil pollutant concentrations under a specific willow plantation (Salix miyabeana 'SX61' and 'SX64'), even after almost a decade of cultivation [6,17], contrary to initial hypotheses and objectives. The main findings concerning the establishment (first year) of this plantation can be found in Guidi et al [6].…”
Section: Introductionmentioning
confidence: 66%
“…At the beginning of the fifth growing season (corresponding to the T0 in Fortin Faubert et al [17]), all analyzed contaminants on the site were found in significantly higher concentration under willows than under the control treatment. We hypothesized that the absence of convincing soil decontamination under the willow plantation could be attributable to the attraction of the dissolved contaminant fraction towards the root zones, facilitated by the high evapotranspiration rate of willow fields under SRIC management.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations